The link between the range of rapid weight loss and physical conditions of elite wrestlers during competition under the morning weigh-in rule - Kondo, E.; Nishimaki, M.; Yamashita, D.; Nakajima, K. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Amateur wrestlers have often undergone rapid weight loss (RWL) to win their matches. On January 1, 2018, the rule of weigh-in was changed and weight category increased. The study aimed to determine the prevalence of wrestlers undergoing RWL under the new rule of morning weigh-in before the tournament and examine the relationship between the range of RWL and physical conditions. METHODS: Male (N=204) and female (N=50) wrestlers participating in the National Wrestling Championship completed a questionnaire about weight reduction methods and their physical condition. RESULTS: Among 159 participants exceeding their weight class one-week before competition, 36% of males and 44% of females exceeded their weight class by 0.0-4.9% (requiring small RWL); 30% of males and 6% of females exceeded by 5.0-10.0% (requiring large RWL), but neither males nor females were over 10.0% above required weight. In males, there was a moderate negative correlation between excess rates of body mass one-week before competition and their physical condition (r=-0.330 to -0.467, P<0.05) on the first day of the competition; however, no significant correlation was found in the females. Comparing physical condition according to the range of RWL, there were significantly lower scores in the large RWL group (=4.9%) than the small RWL group (<4.9%) in males. CONCLUSIONS: We found that RWL=5% is most appropriate to ensure better physical condition of wrestlers on competition day.